The First Record of Argulus Foliacesus (Crustacea: Branchiura) Infestation on Lionhead Goldfish (Carassius Auratus) in Iran - AH Shahmoradi; Y Chelongar; V Noaman (Iranian Journal of Parasitology, 2010)
Argulus foliaceus (Crustacea: Branchiura), or the fish louse, is an ectoparasite of the skin or gill of the fresh water fish species. Clinical signs in infected fish include scratching on aquarium walls, erratic swimming, and poor growth. It causes pathological changes due to direct tissue damage and secondary infections. In the present study, lionhead goldfish (Carassius auratus), taken from a goldfish aquarium with symptoms such as abnormal swimming, poor growth and death, were examined for ectoparasites. The parasites collected from the skin and fins of fish were identified as A. foliaceus. Then, treatment was carried out by trichlorfon. After administration, no parasite was observed on the fish. This is the first report of infection with A. foliaceus of lionhead goldfish (Carassius auratus) in Iran.